Woody Guthrie : songs and art * words and wisdom - Guthrie, Woody, 1912-1967 (Chronicle Books, 2021)
"Featuring never-before-published lyrics to some of his greatest songs, personal diary entries, doodles, quips and jokes, and piercing insights on politics and justice, this is Woody Guthrie's essential self-portrait, carefully curated by Woody's daughter Nora Guthrie and award-winning music writer and historian Robert Santelli"--